Health in Ecuador as a fundamental right in the face of the SARS-COV-2 health emergency. - Cevallos Sánchez, Gissela Alexandra; Moncada, Zoila Alvarado (Revista Universidad de Guayaquil, 2024)
This research focused its study on the critical, doctrinal, legal and comparative analysis of the main affectations and conditions caused by Sars-Cov-2, given the weaknesses faced by the states in relation to the constitutional guarantees to the Human Right to Health. The qualitative methodology through the documentary review and the application of the analytical-synthetic, historical-comparative methods, allowed a study of each part of the process, in order to obtain a general result of them, from the understanding of the historical and comparative facts of the subject that explicitly establish a general approach on the responsibility of the State in the face of the Right to Public Health. The public health system in Ecuador should be considered a priority and its financing should come mostly from the budget allocated by the State to the public health portfolio, so that objective health care programs can be implemented, that focus on the attention of emergencies such as Covid-19, and that do not take by surprise the fragility of the public health system. This budget should be allocated especially to the hiring of specialized personnel, medical equipment for the operation of hospitals and medicines, which guarantee priority attention in terms of the health system to citizens. Keywords: Right to Health, State Responsibility, Covid-19, Pandemic.